Teaching English for Specific Purposes through Task-Based Approach in A Hospitality College - Budi Purnomo (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This research is intended to investigate the effectiveness of teaching English for Specific Purposes (ESP) through task-based approach in a hospitality college. This research is of a descriptive and qualitative study. It uses six stages: pre-task, task, planning, report, analysis, and practice (British Council, 2018) along with three techniques for collecting data: observation, questionnaire and in-depth interviewing. There were 34 students of Hotel Department at Sahid Tourism Institute of Surakarta and an English lecturer prepared as research subjects. The research findings show that: (1) students were very active in teaching and learning ESP through task-based approach; (2) students used their ESP in authentic situations that felt like the “real world”; and (3) at the end of the teaching and learning process, their knowledge of ESP improved. The findings indicate strongly that not only do the teaching English for Specific Purposes through task-based approach develop the students’ English speaking skills effectively, but also increase their hospitality knowledge.